Embolic central retinal artery occlusion as a complication of percutaneous coronary angioplasty – case report - Kraśnicki, Paweł; Proniewska-Skrętek, Ewa; Mariak, Zofia; Dubicki, Artur; Mężyński, Grzegorz; Dobrzycki, Sławomir (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Procedures of the percutaneous coronary intervention are more often carried out in patients with coronary heart disease (CHD) because they are not very invasive and very effective. Even though a lot of procedures of this type are carried out, reports on the ophthalmic complications connected to them,are rarely found. The authors present the case of the 78 years old patient in whom disturbances of the right eye vision occurred after coronary angiography combined with angioplasty of the narrowed artery with stent implantation. Ophthalmic examination revealed features of the central retinal artery occlusion. Even though an immediate treatment was applied, the function of the right eye was not improved. When general condition of the patient was normalized, the diagnosis was confirmed by the Color Doppler ultrasonography in the vessels supplying eye. The photographic documentation was prepared. The literature data indicate the necessity of immediate diagnosis of even mild vision disturbances in the course of and after the percutaneous coronary intervention because only an immediate treatment can protect the patient from a permanent vision decrease, due to the embolism of the retinal vessels.